Differential planetary mechanism of reduction gear for robotic applications - Lee, Bumjoo; Kim, Donghan; Hong, Young Dae (Proceedings of the Institution of Mechanical Engineers, Part C: Journal of Mechanical Engineering Science, 2018)
This study proposes a novel planetary gear mechanism composed of normal spur gears. Similar to a harmonic drive system, one pair of gears generates differential angular motion to achieve a high reduction gear ratio. While a harmonic drive system utilizes slightly different number of gear teeth between the flex spline and the circular spline to induce differential motion, a planetary gear mechanism with different gear modules is adopted for this purpose in the proposed system. Since the manufacture of special components like the wave generator and flex spline in harmonic drive system is not required here, the machinability and usability are improved. In addition, the mechanism can be achieved with a flat shape, which is crucial for various applications such as robotic systems. After the basic concept and three-dimensional design are introduced, the prototype system is presented.
Keywords: differential motion; Planetary gear mechanism; Planetary Gears; Planetary mechanisms; Prototype system; Reduction gear; Robotic applications; Three-dimensional designs; differential motion; planetary gear; Reduction gear